O pewnym ślubnym zwyczaju w relacji Marka Terencjusza Warrona - Hartleb-Kropidło, Barbara (Collectanea Philologica, 2020)
This article focuses on a certain wedding custom presented by the ancient Roman scholar, Marcus Terentius Varro in his work De vita populi Romani. According to him Roman bride on her way to her new home used to carry three coins, and to dedicate them to her husband, to Household Lares and to Compital Lares.